Correlation between the Nonperfusion Area on Ultra-Widefield Fluorescein Angiography and Nonflow Area on Optical Coherence Tomographic Angiography in Retinal Vein Occlusion - Jianfeng Huang; Yingyi Lu; Xiaoya Gu; Bodi Zheng; Tong Chen (Journal of Ophthalmology)
Aims. To compare the relationship between the nonperfusion area (NPA) on ultra-widefield fluorescein angiography (UWFFA) and the nonflow area (NFA) on optical coherence tomographic angiography (OCTA) in retinal vein occlusion (RVO). Methods. Cross-sectional study. 46 eyes of 46 RVO patients who underwent UWFFA and OCTA. NPA and ischemic index (ISI) were quantified on UWWFA. NFA, vessel density (VD) of the superficial capillary plexus (SCP), the deep capillary plexus (DCP), and the size foveal avascular zone (FAZ) on 3 ∗ 3 mm OCTA were measured. The association of the NPA and ISI on UWWFA and the parameters on OCTA were analyzed. Spearman correlation was used for statistical testing. Results. The NPA and ISI on UWFFA were significantly correlated with the NFA on OCTA in RVO, and r values were 0.688 (p<0.01) and 0.680 (p<0.01), respectively. VD in the SCP of the temporal quadrant was negatively correlated with NPA and ISI, and r values were −0.346 (p<0.05) and −0.337 (p<0.05), respectively. VD in the DCP of the temporal quadrant was negatively correlated with the NPA, and the r value was −0.246 (p<0.05). No significant correlation was found between the NPA and ISI on UWFFA and VD of other quadrants in the SCP or DCP and the FAZ area on OCTA. Conclusion. NPA in the peripheral retina was correlated with NFA in macula. NFA detected by OCTA could be an indicator of the ischemic status in RVO.